Matrescence and the Patriarchal African Culture: A Critical Analysis of Buchi Emecheta's The Joys Of Motherhood - Ogbeide-Ihama, Mojisola Amenze Ogbeide-Ihama (African Journal of Stability and Development (AJSD), 2025)
This study examines the concept of matrescence, the developmental process of becoming a mother within the context of patriarchal African culture, as depicted in Buchi Emecheta's seminal novel The Joys of Motherhood (1979). This study, through literary analysis, examines how traditional African patriarchal systems impede and constrain the formation of women's maternal identities, examining how motherhood can both empower and oppress women at the same time. Using close reading methods and theories about how women change when they become mothers, this research looks at how cultural expectations about maternal sacrifice affect women's independence and psychological growth. The study focuses on Emecheta's main character, Nnu Ego, to understand how women form their identity as mothers in societies that both honour and limit motherhood. The research uses feminist and postcolonial approaches to examine the complex relationship between what culture expects from mothers and women's personal freedom. The findings show that motherhood is complicated, it can both restrict women and give them power, as traditional gender roles both limit and create opportunities for women to act independently. This research adds to academic discussions about gender, culture, and maternal identity in postcolonial African literature, providing clear insights into how feminist theory and cultural representation work together in contemporary literature.